Early child development and caregiver subjective well-being in rural China. Issue 2 (29th October 2020) - Luo, Renfu; Lyu, Qijia; Rozelle, Scott; Wang, Shun
Abstract : Purpose: This study aims to bridge the gaps in the existing literature by studying the links between children's development and the subjective well-being of the caregivers using first-hand data collected in rural China. Design/methodology/approach: Although the broad array of literature has examined the effects of child development on the subjective well-being of caregivers, the relationship between early childhood development and caregiver subjective well-being has not been well-studied using sample families with potential developmental delay in rural China. Also, existing research has relied on maternal reports to evaluate the developmental status of children. The study used data collected from 32 townships in seven nationally designated poverty counties in the Qinling mountainous area in 2016. The authors measure child development using the social-emotional module of the Ages & Stages Questionnaire and Bayley Scales of Infant and Toddler Development–Third Edition. Findings: The authors find that child development indicators are correlated with caregiver subjective well-being. In particular, social-emotional skills are positively associated with life evaluations and positive emotion. However, we do not find any significant correlation between child development and negative emotion or depression, anxiety and stress scores. Originality/value: The value of this study is to report the indicators of child development in rural China and examines the correlation between child development and caregivers' subjective well-being.